Cell-mediated immunity induced in mice after vaccination with a protease activation mutant, TR-2, of Sendai virus. - Tashiro, M (1988)
Our previous study has shown that, although a trypsin-resistant mutant of Sendai virus, TR-2, replicates only in a single cycle in mouse lung with a negligible lesion, the animal acquires a strong immunity against lethal infection with wild-type Sendai virus, suggesting that TR-2 could be used as a new type of live vaccine (M. Tashiro and M. Homma, J. Virol. 53:228-234, 1985). In the present study, we investigated the immunological response elicited in TR-2-infected mice, particularly with respect to cell-mediated immunity. Analyses of cytotoxic activities of spleen cells with 51Cr release assays revealed that Sendai virus-specific T lymphocytes (CTL), in addition to natural killer activity and antiviral antibodies, were induced in DBA/2 and C3H/He mice infected intranasally with TR-2. Proteolytic activation of the fusion glycoprotein F was required for the primary induction of CTL, though not necessarily for stimulation of natural killer and antibody responses. Memory of the CTL induced by TR-2 was long-lasting and was recalled in vivo immediately after challenge with wild-type Sendai virus. In contrast to TR-2, immunization with inactive split vaccine failed to induce the CTL response, but it elicited a high titer of serum antibody and a low level of natural killer activity.